Peripheral pulmonary stenosis with Noonan syndrome treated by balloon pulmonary angioplasty - Ko, Seien (Pulm Circ, 2020)
Noonan syndrome is known to have various cardiovascular defects, which include pulmonary artery stenosis. Pulmonary artery stenosis is characterized by obstruction of pulmonary artery blood flow that can cause elevated pulmonary artery pressure and ventilation-perfusion inequality, which can cause dyspnea on exertion and eventually, heart failure. Although the etiology of pulmonary artery stenosis related to congenital diseases is still unknown, balloon pulmonary angioplasty has being reported to be effective to selected patients with Alagille and Williams syndromes, but not from Noonan syndrome despite of modest prevalence of pulmonary artery stenosis. Here, we report the first Noonan syndrome patient with pulmonary artery stenosis who underwent successful balloon pulmonary angioplasty. The strategy used in balloon pulmonary angioplasty was planned with careful morphologic evaluation by computed tomographic angiography, and performed with scoring balloons in a graded approach with multiple sessions. After balloon pulmonary angioplasty, we confirmed maintained dilation of lesions and symptom alleviation, suggesting that balloon pulmonary angioplasty can be performed safely on pulmonary artery stenosis in a Noonan syndrome patient.